A Study of Parasitic Copepod Infesting Two Freshwater Fish Populations (Cyprinus carpio and Abramis brama) from Beni-Haroun Dam (Mila) North-East of Algeria - Berrouk,H; Tolba,M; Touarfia, M; Boualleg,Ch. (My University, 2020)
Copepods are one of the main fish ectoparasites, commonly known among the parasitism world, due either to their special adaptive capacity or to induce stress in aquatic organisms, as well as the parasitism result is overall a physiological rate affecting the survival of host. This study was, therefore, aimed to investigate the ectoparasite copepods, infesting 277 fishes including 135 of Cyprinus carpio (Linnaeus, 1758) and 142 of Abramis brama (Linnaeus,1758), collected from BeniHaroun dam (Mila, northeast Algeria). The fishes were subjected to some morphometric measurements and gill dissections and the harvested parasites were afterwards stored and identified. The parasitic indices were determined to examine the effect of size, sex, season and